Sol-gel synthesis of zinc oxide nanoparticles using Citrus aurantifolia extracts - Ain Samat, N.; Md Nor, R. (2013)
The use of plant extract in the synthesis of nanostructured materials can be a cost effective and eco-friendly approach. In this paper we report the biosynthesis of zinc oxide nanoparticles using Citrus aurantifolia extracts. Spherical zinc oxide nanoparticles were produced using different concentration of zinc acetate which was used as the zinc source. FESEM imaging showed the formation of nanoparticles in the size range of 50-200 nm. XRD analysis revealed wurtzite hexagonal ZnO with preferential orientation at (1 0 0) reflection plane. The room temperature PL spectroscopy showed little variation for samples deposited with different zinc acetate concentration. Peak due to V o +, Vo, hole trapped at Vo, O i and hydroxyl groups were observed with slight variation in peak position. The synthesis of zinc oxide nanoparticles using the citrus extracts were found to be comparable to those obtained from conventional reduction methods using hexamethylenetetramine or cetyltrimethylammonium bromide and can be an excellent alternative for the synthesis of ZnO nanoparticles using biomaterials. Â© 2012 Elsevier Ltd and Techna Group S.r.l.